The Use Complementary and Alternative Practices among Adult Patients with Diabetes Mellitus: An Example of University Hospital - Aktura, Seher Çevik; Evren, Bahri; Sarıtaş, Seyhan Çıtlık; Sahin, İbrahim (My University, 2025)
Aim: The consequences of diabetes mellitus (DM) have a serious impact on the quality of life. As the results obtained from diabetes management are not satisfactory for some patients, they resort to complementary and alternative practice (CAP) methods. The study was conducted in order to examine the patients with diabetes mellitus who use and do not use CAP according to various variables. Material and Methods: The study was designed as a cross-sectional study. The data were collected between January-July 2020. The research was carried out at endocrine service and outpatient clinics of a university hospital. The data were analyzed using descriptive statistics, and chi-square analysis. Results: In the study, it was determined that 21% of diabetic patients used one of the CAP methods and mostly preferred herbal tea [chamomile, green tea, clove, sage, thyme] and cinnamon. It was found that 54,5% of the patients used CAP practices during the treatment process, 31,8% as soon as the diagnosis was made, 11,4% before treatment and 2.3% after treatment. In the study, 70,5% of the patients stated that they knew the effect of the CAP method they used, 56,8% found the CAP method useful, and 81,8% stated that they had no health problems related to the method they used. It was found that 43,2% of the patients used CAP for 1-3 months, 47,7% used it every week. Conclusion: It was observed that patients with DM who participated in the study frequently used CAP methods to reduce/stabilise blood glucose levels and mostly used information teas and cinnamon. It was observed that half of the patients received information about the CAP method from neighbours/friends and only one third of the patients stated that they benefited from the CAP method they used.
Keywords: Diabetes mellitus; Patient; Complementary and alternative practices